Supervision Practice in the Face of Emerging Health Risks: How Market Dynamics are Forcing Enforcement Officials to Stretch their Mandate - Aute Kasdorp (Utrecht University School of Law, 2019)
The modern health care landscape is increasingly hard to capture in regulation and difficult to control by supervision agencies since, due to technological innovation and societal developments, new products and new health risks often emerge that extant regulation does not cover adequately. To counteract potentially harmful conduct, supervision agencies may frequently apply pressure on regulatees through regulatory conversations or negative publicity, even if their conduct may be legal. In this paper we provide context for such interventions beyond the law, outline the broad range of such interventions and discuss their efficacy and legitimacy. We recommend that relevant stakeholders engage in a dialogue that may result in institutional guidelines for supervision agencies on informal supervision practices and interventions beyond the law.